Distribution and Diversity of Myxomycetes Along the Elevational Belt of Mt. Calavite Wildlife Sanctuary (MCWS), Occidental Mindoro, Philippines - Christon Jairus M. Racoma; John Carlo Redeña-Santos; Nikki Heherson A. Dagamac (Ecologies)
Myxomycetes are protists that predate microbial communities in soil and are heavily affected by changing climate conditions. As seen in a more distinct guild of myxomycete, their fructification diversity depends not only on the heterogeneity of vegetation but also on temperature and precipitation. To determine the reverse pattern of microbial diversity established in temperate ecozones, foliar and lignicolous litters were collected along a tropical montane site in the Philippines. Fifty-seven (57) morphospecies of myxomycetes from 15 genera were determined. Alpha-diversity analysis revealed a significant decline in species richness and diversity with increasing elevation. Beta-diversity analysis, integrating non-metric multidimensional scaling (NMDS), PERMANOVA, and hierarchical clustering, revealed the complex relationships between species turnover and community composition across elevational gradients. These results conform to the hypothesis that species richness decreases as elevation increases, supporting that tropical ecozones follow the general trend of myxomycete diversity that was first observed in the temperate ecozones. The strong role of elevation in shaping myxomycete community structure is further emphasized. This indicates that conservation management efforts should become more stringent in the areas found at the lower elevation of a tropical montane forest, which are more ecologically sensitive to human-induced stressors and climate-related pressures.